Bifidobacterium lactis BB-12 Attenuates Macrophage Aging Induced by D-Galactose and Promotes M2 Macrophage Polarization - Da-yong Zhang; Zheng-yang Pan; Xiong-kai Yu; Yi-fan Chen; Chen-hao Gao; Yu-tian Yang; Xue-fan Jiang; Na Li; Jian-ping Pan (Journal of Immunology Research)
Immunosenescence comprises a set of dynamic changes occurring in innate and adaptive immune systems, and macrophage aging plays an important role in innate and adaptive immunosenescence. However, function and polarization changes in aging macrophages have not been fully evaluated, and no effective method for delaying macrophage senescence is currently available. The results of this study reveal that D-galactose (D-gal) can promote J774A.1 macrophage senescence and induce macrophage M1 polarization differentiation. Bifidobacterium lactis BB-12 can significantly inhibit J774A.1 macrophage senescence induced by D-gal. IL-6 and IL-12 levels in the BB-12 groups remarkably decreased compared with that in the D-gal group, and the M2 marker, IL-10, and Arg-1 mRNA levels increased in the BB-12 group. BB-12 inhibited the expression of p-signal transducer and activator of transcription 1 (STAT1) and promoted p-STAT6 expression. In summary, the present study indicates that BB-12 can attenuate the J774A.1 macrophage senescence and induce M2 macrophage polarization, thereby indicating the potential of BB-12 to slow down immunosenescence and inflamm-aging.